EXTRACTION AND PARTIAL PURIFICATION OF PEROXIDASE FROM LOCAL LYCOPERSICON ESCULENTUM - Soud, Asmaa (Iraqi Journal of Science, 2024)
An investigation was conducted to evaluate the peroxidase enzyme in local tomato included tomato’s skin and flesh for each green, semi ripe, ripe and whole tomato fruit. The results indicated the highest peroxidase specific activity was in the whole tomato fruit 16 unit / mg protein . The sodium acetate 0.1M buffer was the best extraction solution of peroxidase from tomato fruit and specific activity was 32 unit mg protein protein. The enzyme was purified in to two steps including precipitation by ammonium sulfate with 85 % saturation followed by ion exchange chromatography on DEAE – Sephadex – A 50 which showed 6 as fold of purification and 53.7 % as enzymatic yield .